Controlled Bidirectional Quantum Secure Direct Communication - Yao-Hsin Chou; Yu-Ting Lin; Guo-Jyun Zeng; Fang-Jhu Lin; Chi-Yuan Chen (The Scientific World Journal)
We propose a novel protocol for controlled bidirectional quantum secure communication based on a nonlocal swap gate scheme. Our proposed protocol would be applied to a system in which a controller (supervisor/Charlie) controls the bidirectional communication with quantum information or secret messages between legitimate users (Alice and Bob). In this system, the legitimate users must obtain permission from the controller in order to exchange their respective quantum information or secret messages simultaneously; the controller is unable to obtain any quantum information or secret messages from the decoding process. Moreover, the presence of the controller also avoids the problem of one legitimate user receiving the quantum information or secret message before the other, and then refusing to help the other user decode the quantum information or secret message. Our proposed protocol is aimed at protecting against external and participant attacks on such a system, and the cost of transmitting quantum bits using our protocol is less than that achieved in other studies. Based on the nonlocal swap gate scheme, the legitimate users exchange their quantum information or secret messages without transmission in a public channel, thus protecting against eavesdroppers stealing the secret messages.